Mapping the Landscape of the Digital Workflow of Esthetic Veneers from Design to Cementation: A Systematic Review - Walaa Magdy Ahmed; Amr Ahmed Azhari; Lamer Sedayo; Alanod Alhaid; Reem Alhandar; Amirah Almalki; Aishah Jahlan; Afnan Almutairi; Waad Kheder (MDPI AG, 2024)
The purpose of this systematic review was to map all the existing literature on digitally designed and fabricated esthetic veneers. We aimed to compare the accuracy of digitally designed preparation and cementation guides for esthetic indirect veneers with the conventional workflow. We evaluated studies comparing the accuracy and predictability of workflows between digitally fabricated indirect-esthetic veneers and conventional indirect veneers. Searches were performed in August 2023 across three databases, specifically Google Scholar, Cochrane, and PubMed, and were restricted to English-language publications. The search strategy was based on the PICO criteria. Reference lists of identified articles were manually checked to find further pertinent studies that were not discovered during the electronic search. The titles and abstracts were reviewed in the first stage, and then the full article texts were reviewed and cross-matched against the predetermined inclusion criteria. Following the search, 169 articles were identified: 41 from Google Scholar, 44 from Cochrane, and 71 from PubMed, with 13 added manually. Of these, 20 were chosen for a detailed quality assessment of the digital veneer workflow and the accuracy of digital preparations and cementation guides for laminate veneers. Based on our findings, the digitally fabricated laminate-veneer workflow demonstrated superior predictability and accuracy compared to the conventional workflow.